The Effectiveness of Bulk Polymerization and Precipitation Polymerization on the Adsorption Capacity of Pb(II) Metal Ions Using Ionic Imprinted Polymer (IIP) (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2024)
Lead (II) metal is a heavy metal that has high toxicity and is easily decomposed, causing long-term adverse effects on the environmental and human health. Therefore, it is important to develop a separation method to effectively detect lead (II) metal ions in water so that it can reduce adverse effects on humans, organisms and aquatic biota. Lead ion imprinted polymer (Pb-IIP) was developed to detect Pb(II) metal ions in water. The commonly used polymerization methods are bulk and precipitation polymerization, therefore this study aims to determine the effectiveness of the adsorption ability of Pb(II) metal ions in water using bulk polymerization and precipitation polymerization methods. The IIP was successfully prepared using Pb(NO3)2 as a template, methacrylic acid (MAA) as a functional monomer, ethylenegycoldimethacrylate (EGDMA) as a crosslinker, benzoyl peroxide (BPO) as an initiator and etylenediaminetetraacetic acid (EDTA) as a chelating ligand. Based on the study, the IIP polymerization method using precipitation polymerization produces adsorbents that have good quality, high adsorption capacity and small particles even though both methods are selective for Pb(II) metal ions. The adsorption capacity of precipitation polymerization is (56,23 mg/g) and the adsorption capacity of bulk polymerization is (46,24 mg/g).